Invictus: Race and Emotional Labor of Faculty of Color at the Urban Community College - Kerri-Ann M Smith; Kathleen T. Alves; Irvin Weathersby Jr.; John D. Yi (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
This article shares the counter-stories of four junior faculty members of color, whose lived experiences provide concrete examples of what emotional labor sometimes entails in higher education. Grounded in Critical Race Theory and antiracist methodologies, these academics identify specific ways in which they experience emotional labor: guilt, silence, anger, navigating double-consciousness and liminality, and self-regulating physical and mental health. They seek to buttress their experiences with counternarratives and, consequently, recommendations for how community college leaders may help to alleviate the emotional labor associated with junior faculty members of color through promotion, leadership, mentoring, and recognition of diverse perspectives and contributions by faculty members of color to the landscape of academe.
Keywords: Education; Emotional Labor; Critical Race Theory